Forward : a memoir - Wambach, Abby, 1980- (Dey Street Books, 2016)
"Abby Wambach has always pushed the limits of what is possible. Named by Time magazine as one of the most influential people of 2015, the iconic soccer player captured the nation's heart when she led her team to its recent World Cup Championship. Admired for her fearlessness and passion, Abby is a vocal advocate for women's rights and equal opportunity, pushing to translate the success of her team to the real world. She has become a heavily requested speaker to a wide a range of audiences, from college students to executives at Fortune 500 companies. In Forward, Abby recounts her own decisions, wins, losses, and the pivotal moments that helped her become the world class athlete and leader she is today. Wambach's book goes beyond the soccer field to reveal a soulful person grappling universal questions about how we can live our best lives, and become our truest selves. Written with honesty and heart, Forward is an inspiring blueprint for individual growth and rousing call to action"--